2017
DOI: 10.4018/ijphim.2017070105
|View full text |Cite
|
Sign up to set email alerts
|

Videogames as Therapy

Abstract: Thereisalonghistoryofusingvideogamesinatherapeuticcapacityincludingrehabilitationfor strokepatients,peoplewithtraumaticbraininjuries,burnsvictims,wheelchairusers,Erb'spalsy sufferers,childrenundergoingchemotherapy,childrenwithmusculardystrophy,autisticchildrenand individualslookingtoovercomereal-lifechallenges(includingsymptomsofdepression)andboost theirwellbeing(includingboostinglifesatisfaction,self-efficacyandsocialsupport).Thispaper brieflyandselectivelyexaminesanumberofareasincluding:(1)videogamesasphysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 107 publications
1
14
0
1
Order By: Relevance
“…This is in line with previous research (82) showing that video games have many beneficial effects on gamers (both genders, young and old) and are used in various contexts, including video games as physiotherapy and occupational therapy, distractors in the role of pain management, cognitive rehabilitation, improvement of social and communication skills among the learning disabled, alleviating symptoms of impulsivity/attention deficit disorders, therapeutic benefits in the elderly, psychotherapeutic settings, health care, treatment of anxiety disorders, and psychological well-being. Moreover, experimental research (83) indicates that playing video games can result in improved task-switching, better top-down attentional control (rather than bottom-up) and processing speed, and increased and quicker time perception.…”
Section: Discussionsupporting
confidence: 94%
“…This is in line with previous research (82) showing that video games have many beneficial effects on gamers (both genders, young and old) and are used in various contexts, including video games as physiotherapy and occupational therapy, distractors in the role of pain management, cognitive rehabilitation, improvement of social and communication skills among the learning disabled, alleviating symptoms of impulsivity/attention deficit disorders, therapeutic benefits in the elderly, psychotherapeutic settings, health care, treatment of anxiety disorders, and psychological well-being. Moreover, experimental research (83) indicates that playing video games can result in improved task-switching, better top-down attentional control (rather than bottom-up) and processing speed, and increased and quicker time perception.…”
Section: Discussionsupporting
confidence: 94%
“…Playing video games has become one of the most valued entertainment options for approximately 2.34 billion individuals (Statista, 2018). Research has confirmed that gaming can have many positive educational, social, and therapeutic effects in a healthy context (Colder Carras et al, 2018;Granic, Lobel, & Engels, 2014;Griffiths, Kuss, & Ortiz de Gortari, 2017;Nuyens, Kuss, Lopez-Fernandez, & Griffiths, 2018). However, for a minority of individuals, gaming is used in a dysfunctional way, becoming disruptive and potentially meeting criteria for addiction (Griffiths, 2005;Pontes & Griffiths, 2015b) with impacts experienced on a cognitive, psychological, and emotional level.…”
Section: Introductionmentioning
confidence: 99%
“…Research evidence suggests that most engagement in gaming is of positive benefit (Griffiths 2019) and that the benefits can by educational, physical, and therapeutic (Griffiths et al 2017). Gaming can also help in developing cognitive skills such as reasoning, spatial awareness, and problem-solving (Bowen 2014;Nuyens et al 2019).…”
mentioning
confidence: 99%